Prognosis of the co-morbid heart failure and anaemia: a systematic review and meta-analysis - Kyriakou, Martha; Kiff, P.; Lambrinou, Ekaterini (My University, 2015)
Anemia is found to be an independent risk factor of morbidity, mortality andhospitalization among patients with heart failure (HF). Over t he last decade, theprevalence, as the potential treatment options of anaemia in HF have receivedincreasing clinical interest and epidemiological studies have indicated a wide varia-tion in the prevalence of anaemia in patients with chronic HF.The goal of the present systematic review and meta-analysis was to investigatethe prognosis of comorbid anaemia in patients with HF. The clinical outcomesunder investigation were: the mortality rate, the re-hospitalization rate, the lengthof hospital stay and the association between the co-morbidity of aneamia and thephysical functionality of the patients according to NYHA classication.Electronic search took place in the databases: Pubmed, Cochrane Library andCINAHL. The combination of the words: “heart failure”, “anaemia”, “readmission”and “NYHA class” was used for the search in order to locate studies in Englishlanguage that investigated the effect of anaemia in patients with HF outcomes. Theoverall pooled effect (relative risk, RR) of anaemia as comorbid factor compared withHF patients without anaemia by using a random effects analysis (95% condenceinterval (CI) for the outcomes of HF - related mortality rate, re-hospitalization andphysical condition.
Keywords: Heart failure; Αnemia; Mortality